An examination of the efficacy and safety of fenfluramine in adults, children, and adolescents with Dravet syndrome in a real‐world practice setting: A report from the Fenfluramine European Early Access Program. Issue 4 (8th August 2022) - Guerrini, Renzo; Specchio, Nicola; Aledo‐Serrano, Ángel; Pringsheim, Milka; Darra, Francesca; Mayer, Thomas; Gil‐Nagel, Antonio; Polster, Tilman; Zuberi, Sameer M.; Lothe, Amélie; Gammaitoni, Arnold; Strzelczyk, Adam
Abstract: Objective: To examine the efficacy and safety of fenfluramine in patients with Dravet syndrome (DS) in three age groups: <6, 6‐17, and ≥18 years old, treated in a real‐world setting. Methods: Patients with DS were treated with fenfluramine in the European Union Early Access Program (EAP). Following a 28‐day baseline period to establish the pretreatment monthly convulsive seizure frequency (MCSF), fenfluramine was started at a dose chosen by the treating physician and gradually titrated based on efficacy and tolerability up to a maximum of 0.7 mg/kg/day. Seizure incidence was recorded in a written diary, and adverse events (AEs) were reported at each patient visit. Cardiovascular safety was assessed by transthoracic echocardiography before treatment started and at least every 6 months thereafter. Results: A total of 149 patients have enrolled in the EAP and 63 were <6 years old, 62 were 6‐17 years old, and 24 were ≥18 years old. After 3 months of treatment 62%, 53%, and 50% of patients demonstrated ≥75% reduction in MCSF in the <6, 6‐17, and ≥18‐year‐old groups, respectively. This pattern of response was sustained through 12 months of treatment with 55%, 46%, and 80% of the <6, 6‐17, and ≥18‐year‐old groups, respectively, experiencing a ≥75% reduction in MCSF. Most common AEs were loss of appetite (21%) and somnolence (16%). No valvular heart disease or pulmonary artery hypertension was observed. Significance: The magnitude, consistency, and durability of the response to add‐on fenfluramine is consistent across age groups in patients with Dravet syndrome.